ARRANJOS INSTITUCIONAIS PARA A GOVERNANÇA DE RECURSOS HÍDRICOS: uma análise “Coasiana” acerca da tensão entre agricultura e turismo em Bonito (MS) - Danielle Tanaka Munhoz (2023)
Water, abundant in our country, fundamental for human existence, of multiple and strategic use for agribusiness is a finite resource and needs investments in favor of rational use both from the perspective of economic efficiency and sustainability, therefore, it does not of a correct allocation to guarantee future generations its full exercise. Mato Grosso do Sul stands out in the production of grains and new areas were allocated to crops in the state, contributing to the state continuing to stand out in the Brazilian ranking regarding the wealth produced by agribusiness. However, the new cultivation fronts that were not planned can negatively impact the environment and society, an example of this fact is what happens with the scenic rivers of the municipality of Bonito/MS. Having as a point of reference the problem of turbidity in the rivers of the Rio Formoso watershed, the research is conducted in order to understand the role of institutions in addressing tensions between the economic agents involved, especially those related to tourism and agriculture. . The objective is to analyze, from the perspective of the Coase Theorem, the arrangements created for the governance of water resources in Bonito/MS, focusing on the allocation of property rights over the use of surface waters. In this step, a qualitative research was carried out in three stages: the first to characterize the normative instruments involved in the governance of the use of surface water resources existing in Brazil and in Mato Grosso do Sul involving the normative survey that regulate water resources at the federal level , state and municipal; in the second stage, interviews were carried out with sixteen people related to agricultural activity, tourist activity, public agencies and institutions in order to verify the circumstances and reasons, in which there are tensions related to the use of water resources and agricultural activity in Bonito/MS; finally, in the third stage, with the scope of identifying the institutional arrangements related to the governance of the use of water resources in Bonito/MS, there was a case study of the Miranda River Hydrographic Basin Committee – CBHRM and the Technical Chamber of Conservation of the Soil and Water (CTCSA). The research result reveals that the investigated institutional arrangements are effective in the governance of water resources. Each of the arrangements has its relevance. CBHRM, as it operates throughout the Miranda river basin, operates in a comprehensive manner. Regarding the CTCSA, its relevance is evident, since when dealing with soil and water conservation, it presents a swift and effective action in resolving disputes involving soil movement that impact water resources in Bonito/MS. Thus, the importance of institutions is evident, as well as the complementarity between formal institutions and institutional arrangements, for the minimization of transaction costs and alignment of interests between the parties involved. Keywords: Water; natural resources, Coase theorem; institutions; property right; Contamination.